2011
DOI: 10.1111/j.1467-7652.2011.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Brassica juncea wild‐type and mutant HMG‐CoA synthase 1 in Arabidopsis up‐regulates genes in sterol biosynthesis and enhances sterol production and stress tolerance

Abstract: SummaryBrassica juncea 3-hydroxy-3-methylglutaryl-CoA synthase (HMGS) is encoded by four isogenes (BjHMGS1-BjHMGS4). In vitro enzyme assays had indicated that the recombinant BjHMGS1 H188N mutant lacked substrate inhibition by acetoacetyl-CoA (AcAc-CoA) and showed 8-fold decreased enzyme activity. The S359A mutant demonstrated 10-fold higher activity, while the H188N ⁄ S359A double mutant displayed a 10-fold increased enzyme activity and lacked inhibition by AcAc-CoA. Here, wild-type and mutant BjHMGS1 were ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 75 publications
8
105
1
Order By: Relevance
“…We believe that Arabidopsis AtCYP710A1 gene-overexpressing plants have a less-permeable membrane and hence resisted pathogen growth while the Atcyp710A1 mutant compromised both host and nonhost resistance. Recent studies also showed the relevance of stigmasterol in plant-pathogen interaction (Griebel and Zeier, 2010;Wang et al, 2012). Consistent with our results, resistance of 3-hydroxy-3-methylglutaryl-CoA synthase overexpressed Arabidopsis plants to Botrytis cinerea was shown to be due to up-regulation of AtCYP710A1 gene expression and stigmasterol content (Wang et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…We believe that Arabidopsis AtCYP710A1 gene-overexpressing plants have a less-permeable membrane and hence resisted pathogen growth while the Atcyp710A1 mutant compromised both host and nonhost resistance. Recent studies also showed the relevance of stigmasterol in plant-pathogen interaction (Griebel and Zeier, 2010;Wang et al, 2012). Consistent with our results, resistance of 3-hydroxy-3-methylglutaryl-CoA synthase overexpressed Arabidopsis plants to Botrytis cinerea was shown to be due to up-regulation of AtCYP710A1 gene expression and stigmasterol content (Wang et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…Over the past decade, extensive research efforts have demonstrated that BRs can act as regulatory factors in biotic stress responses in plants (52)(53)(54)(55)(56). BZR1 and BZR2 are two key transcription factors that mediate BR signals by regulating downstream gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, the observation that a perturbation of sterol homeostasis may result in substantially different molecular responses is not unprecedented. Silencing of SQS in W. somnifera results in reduced sterol levels and leads to decreased expression of both JA-dependent PR3 and SA-dependent PR1 and PR5 transcripts (Singh et al, 2015), while the expression of Brassica juncea HMG-CoA synthase in Arabidopsis increases the sterol content and activates the expression of the SA-dependent PR1, PR2, and PR5 transcripts with no involvement of the JA pathway in the defense response (Wang et al, 2012a). However, neither the SA nor the JA defense pathway is activated in Pseudomonas syringae-resistant Arabidopsis mutants lacking sterol C22 desaturase (CYP710A1) activity (Griebel and Zeier, 2010).…”
Section: Plants Perceive a Reduction Of Major Sterols As A Stress Signalmentioning
confidence: 99%
“…Some recent reports also point toward a role for sterols in proper plastid development (Babiychuk et al, 2008;Kim et al, 2010;Gas-Pascual et al, 2015). As key components of cell membranes, sterols are dynamic modulators of their biophysical properties, so that changes in the composition of sterols affect membrane fluidity and permeability (Roche et al, 2008;Grosjean et al, 2015) and, therefore, modulate the activity of membranebound proteins (Carruthers and Melchoir, 1986;Cooke and Burden, 1990;Grandmougin-Ferjani et al, 1997) and the plant adaptive responses to different types of abiotic and biotic stress, including tolerance to thermal stress (Hugly et al, 1990;Beck et al, 2007;Senthil-Kumar et al, 2013), drought (Posé et al, 2009Kumar et al, 2015), metal ions (Urbany et al, 2013;Wagatsuma et al, 2015), and hydrogen peroxide (Wang et al, 2012a), and to bacterial and fungal pathogens (Griebel and Zeier, 2010;Wang et al, 2012b;Kopischke et al, 2013).The embryo-lethal phenotype of the Arabidopsis fps1/fps2 double knockout mutants makes it very difficult to assess the biological role of FPP biosynthesis in postembryonic plant development. To overcome this drawback, we generated conditional knockdown Arabidopsis mutants using a chemically inducible artificial microRNA (amiRNA)-based gene-silencing approach to down-regulate FPS gene expression.…”
mentioning
confidence: 99%